KOMPOSISI PLANKTON DALAM ANALISIS STATUS SAPROBITAS PERAIRAN DANAU TAJWID, KECAMATAN LANGGAM, KABUPATEN PALALAWAN, PROVINSI RIAU - Marito, Suniati Togi (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
This research was conducted to examine in more detail the saprobity status of Lake Tajwid based on its plankton composition. The lake is located in Langgam Subdistrict, Pelalawan Regency, Riau Province. This research used a quantitative descriptive approach, while sampling was carried out at three research stations selected to represent the water conditions at each station. The results of the study showed the presence of 39 plankton genus. Phytoplankton was dominated by the Chlorophyta and Bacillariophyta groups, while zooplankton was dominated by Rotifera. Plankton abundance ranged from 2960 to 6360 individuals per liter, indicating that the waters were mesotrophic. The diversity index (H') was >3, indicating that the waters were at a moderate level of stability, while the dominance index (C) was close to 0, indicating that no particular genus dominated the waters. The results of the physical-chemical parameter measurements showed that the water conditions were still within a range that supported plankton survival. Based on the saprobity analysis results, the waters of Lake Tajwid can be classified as Oligo/β-Mesosaprobic, reflecting that the waters are at a level of light to very light pollution.